Diophantine geometry as Galois theory in the mathematics of Serge Lang - Kim, M (American Mathematical Society, 2007)
A remark about the role of Galois theory in Diophantine geometry as reflected in the work of Serge Lang. An entry in `The mathematical contributions of Serge Lang.'